Persepsi Visual Wisatawan Asing Pada Interior Via-Via Cafe, Janur Cafe Dan K-Meal's Resto Di Jalan Prawirotaman Dan Tirtodipuran Yogyakarta - Martino Dwi Nugroho (Institut Seni Indonesia Surakarta, 2010)
Visual perception is one thing that is important for interior designers.The ability of how to view and respond to an order to be a learningdesign in achieving the satisfaction and development of artistic insight.Perception was present and spoke not be separated from an object ofperception, in this study selected objects based on purposive samplingof Via-Via Cafe, Janur Cafe, and K-Meal's restaurant in Jalan Prawirotamanand Tirtodipuran Yogyakarta with variable subjects (foreign tourists)were randomly. This research is descriptive and qualitative methodsof data analysis done by the field data acquisition process is furtl1ercommunicated in the form of descriptive writing and conclusions. Thisstudy aimed to answer the formulation of the problem, namely the visualperception of foreign tourists in the interior of Via-Via Cafe, CafeJanur. and K-Meal's Resto Yogyakarta with variable lighting, colors andshapes. Visual perception of foreign tourists in the interior of Via-ViaCafe is a bright, warm, relaxed I casual, lively. comfortable, inviting,attractive, simple, artistic, natural, fun, 11ommy. modern, universal atmosphere,style living room, family atmosphere, functional. spacious,sweet I beautiful, alive, creative, unique, traditional I ethnic, tranquil,tropical, and life. While tl1e perception on the interior ligl1ting Janur Cafeis enough (not too bright or dark) and dark, monotonous, warm. romantic,relaxed, flat, inviting, interesting, life, close I warm, a little crowded,ethnic, natural, universal I touristic, l1ommy. fun, convenient, simple,and creative. Visual perception in tl1e interior of K-Meal's restaurantis near I warm. comfortable, lively. relaxed, simple, elegant, attractive,inviting, fit, functional, does not fit, creative, and aesthetically. Can beseen that foreign respondents prefer something with a touch of tropicalnatural concept, simple but comfortable and warm, the combination oflocal I traditional and western I cosmopolitan, open space (open terraceI Verandah) with an open kitchen.Keywords: visual perception, interior, cafes and restaurants.